(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2016)
When breast milk is no longer enough to meet the nutritional needs of infants, complementary foods should be added to their diet. It is a very vulnerable period when malnutrition starts in many infants, contributing significantly to high prevalence of malnutrition in under-5 children world-wide. In Bangladesh, complementary feeding (CF) practices are not satisfactory. The objectives of the study were to look into the feeding patterns of under-2 children and to identify the causes which lead mothers/ caregivers to practice inappropriate CF. This cross-sectional study was done in the Pediatric department of Sir Salimullah Medical College Mitford Hospital, Dhaka and in a private chamber from a district town of Bangladesh from October, 2011 to December, 2011. Four hundred mother-child pairs were enrolled by non-random convenience sampling. Different aspects of feeding practices (age of initiation of CF, type of first complementary food, current main complementary food & its quantity, and frequency of CF) were analyzed. Bottle feeding, fast foods and lack of proper family support were most important barriers (p<0.05). High rate of early initiation of CF was mainly due to mothers perception that breast milk alone was not enough (81.8%) and main cause of late initiation was refusal of complementary foods by their babies (48.4%). Feeding practices were mainly influenced by relatives (25%), qualified doctors (15.3%), neighbors (14.5%) & mother-in-laws (13.5%). CF practices are still far from ideal. Strengthening of nutrition education to mothers/caregivers and family members/relatives along with awareness building in the community may change the wrong practices. J Bangladesh Coll Phys Surg 2015; 33(4): 195-201